2006
DOI: 10.1021/ja060328d
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of the Acetals with TESOTf−Base Combination; Speculation of the Intermediates and Efficient Mixed Acetal Formation

Abstract: We report here unexpected highly chemoselective deprotection of the acetals from aldehydes. Treatment of acetal compounds from aldehydes with TESOTf-2,6-lutidine or TESOTf-2,4,6-collidine in CH2Cl2 at 0 degrees C followed by H2O workup at the same temperature caused the conversion of the acetal functions to aldehyde functions. The reaction had generality and was applied to many acetal compounds. Study using various bases revealed the reaction and reached the best combination of TESOTf-base. It was very mild an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

6
4

Authors

Journals

citations
Cited by 117 publications
(70 citation statements)
references
References 19 publications
2
66
2
Order By: Relevance
“…In previous work, we observed that acetal-selective deprotection of substrates containing both an acetal and ketal group can be carried out using a combination of 2,4,6-collidine and triethylsilyl trifluoromethansulfonate (TESOTf). 21,22) In this effort, we found that excess amounts of reagents (3 eq of 2,4,6-collidine and 2 eq of TESOTf) are required in order to promote complete reaction. We also observed that acetals can be deprotected using a combination of TESOTf and a phosphine.…”
Section: Resultsmentioning
confidence: 99%
“…In previous work, we observed that acetal-selective deprotection of substrates containing both an acetal and ketal group can be carried out using a combination of 2,4,6-collidine and triethylsilyl trifluoromethansulfonate (TESOTf). 21,22) In this effort, we found that excess amounts of reagents (3 eq of 2,4,6-collidine and 2 eq of TESOTf) are required in order to promote complete reaction. We also observed that acetals can be deprotected using a combination of TESOTf and a phosphine.…”
Section: Resultsmentioning
confidence: 99%
“…We developed a new chemoselective method for the deprotection of acetals in the presence of ketals using a combination of 2,4,6-collidine and triethylsilyl trifluoromethanesulfonate (TESOTf) [23][24][25] (Chart 1, Eq. 1).…”
Section: Selective Transformations Of Less Reactive Carbonyl Groups Imentioning
confidence: 99%
“…21) In addition, only one method exists for selective deprotection of acetals in the presence of ketals. 22,23) In 1992, Kim et al described a ketone selective dioxolanation reaction that takes place in the presence of an aldehyde. 24) A combination of dimethyl sulfide and trimethylsilyl trifluoromethanesulfonate (TMSOTf) (Chart 15) was used to selectively protect aldehydes by formation of the corresponding O,S-acetal type sulfonium salts in the presence of ketones, and after carrying out selective ketalization of the remaining ketones using Noyori's conditions, rebirth of aldehydes with alkaline work-up gives ketal aldehydes 25) ( Table 8).…”
Section: Lewis Acid and Lewis Base Pairmentioning
confidence: 99%